2019
DOI: 10.1016/j.jenvp.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Outcome expectancy: A key factor to understanding childhood exposure to nature and children's pro-environmental behavior

Abstract: We are very grateful to all the children who participated in this study. We also thank the teachers who kindly received us in their school and the parents who allowed their children to participate. This study was partly supported by the Spanish Ministry of Economy and Competitiveness (Grant number PSI-2013-44939).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 49 publications
2
28
1
4
Order By: Relevance
“…A third limitation is that our study explains 45% of the variance from self-reported PEB. This percentage is similar to the one found in previous studies with children (Collado and Evans, 2019), but other variables such as social norms (Casaló and Escario, 2016) and perceived restorativeness might help us obtain a deeper understanding of children's PEB.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A third limitation is that our study explains 45% of the variance from self-reported PEB. This percentage is similar to the one found in previous studies with children (Collado and Evans, 2019), but other variables such as social norms (Casaló and Escario, 2016) and perceived restorativeness might help us obtain a deeper understanding of children's PEB.…”
Section: Discussionsupporting
confidence: 88%
“…According to previous studies, some of the drivers of children's PEB include frequent contact with nature (Evans et al, 2018;Collado and Evans, 2019;Otto et al, 2019), pro-environmental attitudes (Cheng and Monroe, 2012;Larson et al, 2015), social norms (Casaló and Escario, 2016;Evans et al, 2018), and perceived restorativeness . To the best of our knowledge, there has been little research done on the role played by the child's environment on their PEB, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in this respect the results are controversial. The positive relationships found in this study between PEBs, knowledge of CE, beliefs about environmental behavior, satisfaction with life, and connectedness to nature in a rural environment support the recent study of Collado [33] and the previous ones of Cheng and Monroe [36] and Otto and Pensini [34], where correlations between sustainability, PEBs, and connectedness to nature in a rural environment were found. Our results also support studies in which an association between sustainability and experiences in natural environments was found, both in adults [30,31] and in children [32].…”
Section: Discussionsupporting
confidence: 90%
“…However, the results are controversial. Some research with children has focused on analyzing the role of experiences in natural environments and their relation to PEBs, finding positive relationships between them [33] and an increase in connectedness to nature [34]. Regarding age, connectedness to nature is related to PEBs in both adults [12,27,28] and children [35].…”
Section: Introductionmentioning
confidence: 99%
“…Perilaku ramah lingkungan anak sebenarnya dipengaruhi oleh banyak faktor. Kegiatan mengajak anak-anak kontak langsung dengan alam melalui tempat-tempat terbuka yang menyediakan suasana alami akan mempengaruhi sikap anak lebih peduli lingkungan [3,5,6]. Meski studi studi Isted dan Saphiro [7] mengatakan bahwa anak yang telah mendapatkan pendidikan lingkungan mampu mempengaruhi orangtua dan keluarganya menjadi lebih amah lingkungan, studi Collado et al [8] pada anak usia 9 sampai 13 tahun membuktikan bahwa perilaku ramah lingkungan anak dipengaruhi oleh orangtua, teman baik, dan anak yang lebih tua darinya.…”
Section: Pendahuluanunclassified